Effect of different fungicides on the control of grey mildew disease of cotton - P.D. WANGIKAR, S.K. SHIVANKAR and (Indian Phytopathology, 2002)
A field trial was conducted on H-4 cotton (Gossypium hirsutum L.) to study the effect of fungicides in controlling grey mildew disease in endemic area of Bramhanwada Thadi (Distt. Amravati) for two seasons i.e. 1986-87 and 1987-88. Amongst nine fungicides tested, sulpen 80 WP (0.25%) was found to be the most effective and controlled the disease to the extent of 67.7% followed by dithane Z-78, calixin 80 EC and bavistin 50 WP. Highest disease intensity of 45.1 % was recorded in control plots. Significantly less defoliation, more boll bearing, highest boll weight and increased yield were recorded in all the fungicide treated plots as compared to control plots. Sulpen 80 WP gave the highest cost benefit ratio followed by dithane Z-78.